2008
DOI: 10.2169/internalmedicine.47.1427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Valsartan Addition to Amlodipine on Insulin Sensitivity in Overweight-Obese Hypertensive Patients

Abstract: Objective The aim of the study was to evaluate the effect of valsartan/amlodipine combination on insulin sensitivity in overweight-obese hypertensive patients. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…RAS blockade has been shown to improve insulin sensitivity in individuals with hypertension or glucometabolic disorders [7][8][9]. In line with these data, we found improved insulin sensitivity after 26 weeks VAL treatment compared with PLB.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…RAS blockade has been shown to improve insulin sensitivity in individuals with hypertension or glucometabolic disorders [7][8][9]. In line with these data, we found improved insulin sensitivity after 26 weeks VAL treatment compared with PLB.…”
Section: Discussionsupporting
confidence: 90%
“…In the Nateglinide and Valsartan in Impaired Glucose Tolerance Outcomes Research (NAVIGATOR) trial, RAS blockade with ARB valsartan for 5 years resulted in a 14% reduction in the onset of T2DM in individuals with IGM [6]. The mechanisms by which ARBs lower T2DM risk have partly been attributed to improvements in peripheral insulin sensitivity [7][8][9]. One of the proposed mechanisms responsible includes ARB-induced haemodynamic changes, resulting in increased blood flow with increased glucose and insulin delivery to insulin-sensitive tissues [10].…”
Section: Introductionmentioning
confidence: 99%
“…One of the underlying mechanisms may involve a positive effect of RAS blockers on insulin sensitivity (8). In part, these effects may be a result of hemodynamic changes, increasing skeletal-muscle blood flow, with augmented glucose and insulin delivery to insulin-sensitive tissues (4).…”
mentioning
confidence: 99%
“…In a study conducted in overweight-obese hypertensive patients valsartan/amlodipine combination improved insulin sensitivity significantly more than monotherapy with either components 78 . Another study demonstrated that, in the same type of population,despite their equivalent BP lowering effect, valsartan/amlodipine combination produced a significant enhancement of insulin sensitivity whereas irbesartan/hydrochlorothiazide (HCTZ) combination did not influence it 79 .…”
Section: Metabolic Properties Of Arb/ccb Combinationmentioning
confidence: 96%